Narratives of Filipino Young Adults Who Have Experienced Cheating in Their Romantic Relationships - Amor Joyce De Luna; Carmella Larguiza; Rungduin Teresita (Universitas Ahmad Dahlan, 2024)
This study explored the narratives of young adults who are victims of cheating in romantic relationships. The narratives of ten participants aged 18 to 25 years were examined through in-depth qualitative interviews. It described their experiences, how they cope, and how they form their subsequent relationships. The data were analyzed through thematic analysis, which revealed that participants discovered their partner's infidelity through their social media, friends, or self-discovery. Regardless of gender, this led to traumatic physical, social, and emotional effects. Coping mechanisms varied from unhealthy behaviors, such as engaging in vice and self-harm, to positive ones, such as writing literature. This study is important for Filipino Psychology because it examines the intricacies of healing and relational growth among young adults grappling with infidelity. Understanding cultural contexts provides input for ways of helping focused on resilience and well-being.